(untitled) (Universal International Scientific Journal, 2026)
This article reviews contemporary research in modern physics. It covers quantum mechanics, relativity theory, cosmology, plasma physics, semiconductor and novel materials physics. The paper also discusses modern theoretical physics methods and computational approaches, including mathematical modeling, computer simulations, and artificial intelligence applications for analyzing complex systems. Examples of current research, such as quantum technologies, tokamak plasma experiments, perovskite materials, and Large Hadron Collider studies, are highlighted. The article provides a comprehensive overview of both theoretical and applied advances in physics, illustrating future prospects for scientific and technological developments.